Hypothesized pharmacogenomic and medication influences on tetrahydrocannabinol and cannabidiol metabolism in a cohort of unselected oral cannabis users - Jessica A. Wright; Linda Huang; Basant E. Katamesh; Siddhant Yadav; Abhinav Singla; Ann Vincent (Journal of Cannabis Research)
Abstract Background Differences in cannabinoid metabolism and patient responses can arise even with equivalent doses and formulations. Genetic polymorphisms in genes responsible for cannabinoid metabolism and medications that alter CYP450 pathways responsible for metabolism of cannabinoids may account for some of this variability. Materials and methods A retrospective chart review was conducted on a cohort of unselected patients who had previously completed pharmacogenomic testing and reported oral cannabis use, as defined as “oral” or “by mouth” route of administration. The objective was to identify atypical variants and medications in this cohort and formulate a hypothesis on how these variables influence the metabolism of Tetrahydrocannabinol (THC) and Cannabidiol (CBD). Results Oral cannabis use was confirmed in 71 patients, with an average age of 68.5 years, and primarily white women. Of the 71 patients, 10 had no atypical variants; 31 had atypical variants in CYP2C9; 37 had atypical variants in CYP2C19; 6 had atypical variants in CYP3A4; and 15 had atypical variants in CYP3A5. Of the 71 patients, 5 were taking medications that could interact with THC, and 8 were taking medications that could interact with CBD. Conclusion The results this study reveal the spectrum of hypothesized alterations in THC and CBD metabolism due to atypical genetic variants and medications. The absence of published clinical outcomes in this field renders it challenging to estimate clinical significance of these findings. Until such data become available, clinicians should remain aware of the possibility that atypical variants and medications may impact patients’ responses to THC and CBD.